Hydrocarbon Prospectivity of Surma Group in Sylhet Area in Context of Sequence Stratigraphy (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
This research focuses on studying the Surma Group sediments with an integrated approach of using wireline logs and 2D seismic data from Sylhet structure and outcrop analogy from the Zaflong-Tamabil-Jaintiapur area to explain the geological evolution in the context of sequence stratigraphic framework and its implications to identify the hidden potential of hydrocarbon traps that remains overlooked. The 'SYL-07' well logs divided the encountered sedimentary strata by sequence boundaries (SB) and flooding surfaces (FS) into an upper third-order Lowstand System Tract (3_LST), followed by the third-order Highstand System Tract (3_HST), and underlying third-order Transgressive System Tract (3_TST) which correspond to the Tipam, Boka Bil, and Bhuban formations, respectively. The 3_HST has further been subdivided into fourth-order sequences. Well-to-seismic ties helped in identifying the sequence boundaries in the regional context. Three new prospects in the nose and flank area of the Sylhet structure have been detected based on seismic attributes and log responses. Seismic sweetness attribute anomalies confirmed the existence of these prospects. Rigorous fieldworks provided nineteen facies and seven sets of sedimentary facies associations and helped to establish the sedimentological stacking patterns and corresponding depositional environments. About 2250m lithocolumn constructed from field data revealed four third-order sequence stratigraphic system tracts roughly corresponding to Renji (3_LST), Bhuban (3_TST), Boka Bil (3_HST), and Tipam (3_LST) formations in the bottom-up order, while the obtained facies associations aid in identifying four fourth-order sequences including fourth-order system tracts in the 3_HST. The lithologic column corresponds well with the seismic sections and validates the seismically interpreted third-order system tracts and fourth-order sequences. However, the high-frequency fourth-order system tracts can only be correlated with the log motif patterns due to sub-seismic resolution. The erosional remains of the fourth-order sequences in 3_HST, for instance, the coarsening upward shoreface and shelfal facies topped by transgressive shale, have yielded potential future drilling sites based on seismic attribute and log response analysis. The analogy of field data with well log and seismic data helped the overall evaluation of the hydrocarbon prospectivity of the area.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11(1), 2022: 95-110